A potential phosphorus fertilizer to alleviate the coming "phosphorus crisis"-biochar derived from enhanced biological phosphorus removal sludge - Qian, Tingting (2022)
The coming crisis of phosphate rock depletion initiates the development of various solid waste derived P fertilizer. Enhanced biological phosphorus removal (EBPR) sludge is ideal waste biomass to produce biochar-P-fertilizer. Here, the form and transformation pattern of released phosphorus (P) of EBPR sludge biochar pyrolyzed at different temperatures were comprehensively investigated. As pyrolysis temperature increased, the proportion of released polyphosphates (Poly-P) increased. The main Poly-P released from low-temperature biochar was tripolyphosphates (Tri-P), while those released from high-temperature were Tri-P and cyclic Poly-P. The presence of Ca2+ could strongly inhibit P-release of low-temperature biochar (e.g., pyrolyzed at 400 °C, E400) but had little effect on that of high-temperature biochar (e.g., 700 °C, E700). All the P species released from E400 and E700 could be efficiently utilized by Pseudomonas putida. Except for the cyclic Poly-P released from E700, the other P species could also be efficiently utilized by Escherichia coli. In short, Poly-P in biochar could hardly precipitate with Ca2+ and can be utilized by certain soil microorganisms. Therefore, high-temperature EBPR sludge biochar (>600 °C) containing a high proportion of Poly-P could be ideal P fertilizer. This study provides a new insight on pyrolysis way to recover P from the sludge.